Analisis Teologis tentang Nilai Tanggung Jawab Suami dan Istri dalam Tradisi Angka' di Mala'bo - Mikael Sanda Layuk; Yusran Bongga Upa'; Melki Palele (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to describe the procession and symbolic meaning of the Angka' tradition in customary marriages in Mala'bo, Mamasa, and to theologically analyze the values of husband-wife responsibility it contains. Angka' is a tradition of giving buku lampa (thigh bone) to the groom and buku siruk (rib bone) to the bride as symbols affirming the husband's role as provider and the wife's role as household manager. This research uses a qualitative approach with an ethnographic-phenomenological design and an anthropological model of contextual theology, which regards local tradition as a locus theologicus that can be dialogued equally with biblical texts, particularly Ephesians 5:22-33 and Proverbs 31. Data were collected through in-depth interviews with customary leaders, couples who had undergone Angka', and local church leaders in Mala'bo, then analyzed using the Miles and Huberman interactive model. The findings show that the meanings of buku lampa and buku siruk align with biblical principles of marital responsibility, although a gap was found between the tradition's symbolic ideal and present-day household practice due to shifting socio-economic conditions. The study also finds that the local church has not yet explicitly linked the value of Angka' with biblical teaching on family, opening a pastoral opportunity to integrate this tradition into premarital formation and Christian family counseling in Mamasa.